Técnica civil de identificação de direito à imagem - Bitelli, Marcos Alberto Sant'Anna (2016)
The study aims to: (i) demonstrate that not all features of personality rights are confirmed effectively in the daily exercise of the right of publicity in the contemporary moment; (ii) evidence that the economic use is an inexorable reality that requires the definition of new contours of the right of publicity; (iii) propose to identify limits to the right of publicity; (iv) to propose the identification of principles applicable to legal relations in the economic use of image rights. Rationale: The right of publicity obtained its autonomy in relation to other personality rights and in Brazil, it was raised to a constitutional fundamental right. The Civil Code treated the right of publicity in Article 20 that is subject to severe critics from the doctrine and cause several disputes in Courts, having been challenged its constitutionality. The Federal Supreme Court in the trial of ADI 4815 that had as its backdrop the need for authorization to produce biographies established rational balance between the fundamental rights of freedom of speech and right of publicity, recognizing the precedence of that freedom of speech on such right. The civil law operation can identify limits to the right of publicity in the production of contents that materialize the freedom of speech without having to seek for solution trough some resolution conflict techniques of constitutional rights. Hypothesis: The work brings as hypothesis that the right of publicity, like author s rights, is a personality right that allows the identification of limits to its exercise and to be subject of civil agreements with economic content, without destroying the core of such right or denying its legal nature. Theoretical and methodological aspects: This study develops an evaluation of the rights of publicity in order to initially identify it as a kind of legal status rather than subjective rights, to then integrate it into the personal assets of the person. Methods of the rules of evidence, analysis and synthesis were used to demonstrate the absence of apparent unanimity about the characteristics of the publicity rights. The case law, jurisprudence and the paradigms of foreign law were additional elements to illustrate the hypothesis. Result: The result was the identification of the boundaries of image rights, the principles that should be applied to relations that the image is the object, a proposal for a revision of Article 20 of the Brazilian Civil Code and of the Precedent 403 of the Superior Court of Justice